Energy efficiency in Peru's industries through self-generation and key lessons for advancing corporate sustainability - Prado Chuquillanqui, Gustavo Adolfo (2025)
The objective of this paper is to analyze how energy efficiency and self-generation in Peruvian industries promote environmental sustainability, the green economy, and business competitiveness, highlighting their capacity to minimize expenses, enhance energy reliability, and reduce reliance on the electricity grid by leveraging renewable energy sources. The study is based on a systematic review of information gathered from academic sources, such as papers and master's theses, as well as newspaper reports. This research identifies strategies for optimizing energy consumption in industrial processes and promoting efficient resource management. The results demonstrate that enhancing energy efficiency is imperative for sustainable development in Peru. This approach enables the optimization of resources, the reduction of emissions, and the strengthening of the energy system's resilience through the integration of clean technologies, such as renewable self-generation. In conclusion, combining energy efficiency with self-generation in industries significantly impacts sustainability and business competitiveness. This practice optimizes energy use, reduces operating costs, and lowers emissions, providing economic and environmental benefits. However, widespread implementation faces regulatory, economic, and educational challenges. Therefore, the paper proposes government support to promote technological innovation and establish comprehensive strategies that drive energy efficiency and self-generation. This requires flexible regulatory frameworks, sustainable financial incentives, such as green bonds, and cross-sector collaboration. These measures will optimize energy performance, reduce environmental impact, and strengthen competitiveness in a sustainability-oriented market.